Comparative study of monolithic, bilayer and gradient CVD diamond coatings under dry sliding against alumina; Ceramics International; Vol. 51, iss. 29, pt. B - Gaydaychuk A. V. Alexander Valerievich; Mitulinsky A. S. Aleksandr Sergeevich; Zenkin S. P. Sergey Petrovich; Linnik S. A. Stepan Andreevich (2025, 2025)
Title screen